A New Paradigm for International Business: Proceedings of the Conference on Free Trade Agreements and Regional Integration in East Asia - Djajadikerta, Hadrian Geri (Springer, 2015)
This book offers a collection of studies on regional integration and the dynamic business environment in East Asia. The papers included, originally presented at the 2014 Asia Pacific Business Conference on "Free Trade Agreements and Regional Integration in East Asia," examine the challenges and dynamics in the increasingly integrated East Asian markets and outline a new paradigm for doing international business in the region. The papers address diverse areas related to regional integration, financial markets, investment, trade and capital flow, sustainability, accounting and auditing issues, exchange rates, strategies and the regional business environment. The book provides a valuable resource for practitioners, policy-makers and students who are interested in understanding the vibrant aspects of business in today’s East Asia.